Beyond the Transaction: AI's Role in Shaping Customer Engagement and Loyalty - Kurnia Khafidhatur Rafiah; Cattleya Rejito; Zidny Ilma Hasan (International Journal of Management and Business Economics, 2025)
This qualitative study explains how Artificial Intelligence technology, specifically chatbots and recommendation systems, impact customer engagement and loyalty on online shopping sites in Indonesia, particularly Shopee. Based on in-depth interviews with 25 users, this study examines customer experiences, attitudes, and behaviors. Chatbots have been shown to provide valuable functional engagement by providing quick and efficient answers to simple questions, such as order status and product details. However, their inability to handle complex issues and lack of human interaction mean that users still prefer to interact with humans for more complex issues. On the other hand, AI-powered recommendation systems are highly effective at triggering behavioral and affective engagement. Such one-to-one product recommendations not only impact purchasing decisions and product discovery but also provide the customer with a feeling of being "understood" by the platform, positively affecting customer loyalty. Altogether, the integration of the two technologies enables Customer Relationship Management (CRM) initiatives through its effectiveness and personalization, resulting in greater customer loyalty levels.